[PP.20.05] THE HEMODYNAMIC CHANGE BY SQUATTING IS INDUCED BY DIMINISHED VASCULAR DISTENSIBILITY AND ENHANCED PRESSURE WAVE REFLECTION. (September 2016) - Nawa, T.; Murakami, T.; Shiraishi, M.; Fukuoka, S.; Higashi, K.; Nakajima, H.; Aotsuka, H.
Abstract : Objective: In patients with tetralogy of Fallot, it is well known that "squatting" increases the pulmonary blood flow and improves cyanosis. However, the mechanism of these hemodynamic changes has not been fully elucidated. Our hypothesis is that squatting accelerates pressure wave reflection and it increases after load of systemic circulation. To clarify the mechanism of squatting, the change in arterial pulsatile property induced by squatting was investigated. Design and method: 31 healthy young adults were enrolled in this study. 12 were men and 19 were women, with a mean age of 30 years (range 23 to 43 years). They had a physical checkup within 6 months, and no abnormality was pointed out. None of them took any medication. Blood pressure (BP) was measured in the right brachial artery using an automated oscillometric method during standing and squatting. Second derivative of photoplethysmogram (SDPTG) was recorded using the digital photoplethysmograph (DYNA PULSE SDP-100, Fukuda Denshi, Tokyo, Japan) during standing and squatting. The amplitude of each wave was measured, and the ratios of the amplitudes of early negative wave (b wave) and late re-downsloping wave (d-wave) to amplitude of initial positive wave (a wave), b/a and d/a ratios, were calculated. Baseline measurements in upright position were obtained after 3 min of quiet standing, including BP and SDPTG. Squatting was then performed for 3 min, with body weight positioned over the heels. Both BP and SDPTG were re-examined during squatting. Results: There was no significant difference about heart rate, systolic BP, diastolic BP, and pulse pressure between two situations. The b/a ratio during squatting were higher than that during standing (mean ± SEM, −0.83 ± 0.16 vs −0.69 ± 0.13, P = 0.00037). The d/a ratio during squatting was lower than that during standing (mean ± SEM, −0.16 ± 0.11 vs −0.31 ± 0.10, P < 0.0001). Conclusions: Squatting diminishes the vascular distensibility and enhances the pressure wave reflection. It could improve cyanotic spells in patients with tetralogy of Fallot.